SYNERGIZING PROPHETIC VALUES AND PHYGITAL LEARNING: A HOLISTIC FRAMEWORK FOR CONSCIENCE DRIVEN ENTREPRENEURSHIP EDUCATION - Siti Atwano Pisriwati; Yuwono Hardi; Deny Hadi Siswanto (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
This research aims to explore the implementation of the entrepreneurship program at SMA Muhammadiyah Mlati. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation of "Market Day," and documentation of the P5 (Project for Strengthening the Profile of Pancasila Students) modules. The results indicate that the school successfully synergizes ISMUBA (Al-Islam, Kemuhammadiyahan, and Arabic) values with the Merdeka Curriculum framework. This integration fosters a "conscience-driven" mindset by embedding prophetic traits shiddiq, amanah, fathanah, and tabligh into business practices. Furthermore, the school utilizes a phygital approach, combining physical business laboratories with digital marketing on social media to enhance students' 21st-century competencies. An intensive mentorship system ensures that technical challenges are transformed into learning opportunities through continuous evaluation. The study concludes that the program effectively develops students into commercially competent and socially responsible innovators. To ensure long-term sustainability, it is suggested that the school expands external partnerships with local industries and formalizes certified digital literacy training for its students.